Binding-, intracellular transport-, and biosynthesis-defective mutants of vasopressin type 2 receptor in patients with X-linked nephrogenic diabetes insipidus. - H Tsukaguchi; H Matsubara; S Taketani; Y Mori; T Seido; M Inada (The Journal of Clinical Investigation, 1995)
Nephrogenic diabetes insipidus (NDI) is most often an X-linked disorder in which urine is not concentrated due to renal resistance to arginine vasopressin. We recently identified four vasopressin type 2 receptor gene mutations in unrelated X-linked NDI families, including R143P, delta V278, R202C, and 804insG. All these mutations reduced ligand binding activity to < 10% of the normal without affecting mRNA accumulation. To elucidate whether the receptors are expressed on the cell surface, we analyzed biosynthesis and localization of tagged or untagged receptors stably expressed in Chinese hamster ovary (CHO) cells, using two antibodies directed against distinct termini. Whole-cell and surface labeling studies revealed that the R202C clone had both surface-localized (50-55 kD) and intracellular proteins (40 and 75 kD), similar to the wild-type AVPR2 clone, whereas the R143P and delta V278 clones lacked the surface receptors, despite relatively increased intracellular components. The 804insG mutant cell produced no proteins despite an adequate mRNA level. Immunofluorescence staining confirmed that the R202C mutant reaches the cell surface, whereas the R143P and delta V278 mutants are retained within the cytoplasmic compartment. Thus, R202C, R143P/delta V278, and 804insG result in three distinct phenotypes, that is, a simple binding impairment at the cell surface, blocked intracellular transport, and ineffective biosynthesis or/and accelerated degradation of the receptor, respectively, and therefore are responsible for NDI. This phenotypic classification will help understanding of molecular pathophysiology of this disorder. Images